Effect of government expenditure towards economics growth in Malaysia / Muhammad Noorhakim Maula Ahmad Ghazi - Ahmad Ghazi, Muhammad Noorhakim Maula (2020)
For decades, the connection between government expenditures and economic growth has been explored, however has not yet been explicitly defined. In the case of Malaysia, this paper provides further evidence regarding the relationship between government expenditure and economic growth. For the last 47 years we used the OLS methods to estimate the fixed effects of government spending on economic growth. This research is performed using data from the time series for the duration 1970 to 2018. To concentrate on the success of economic growth policies and prevent any distortion from unproductive spending, this analysis uses only government development spending rather than government consumption. The test runs on the transportation, military and defense, education, and general administration areas. The results show that only the education areas are important towards economic growth. These results that offer the Malaysian policymakers some outlook of the policy consequences of leveraging the impact of government spending on economic growth.